Thermoplastic elastomer nanocomposites with controlled nanoparticles dispersion for HV insulation systems: Correlation between rheological, thermal, electrical and dielectric properties. (September 2017) - Helal, Emna; David, Eric; Fréchette, Michel; Demarquette, Nicole R.
Graphical abstract: Highlights: Dispersion of ZnO in thermoplastic elastomer tailored by maleic anhydride graft. Tuned dispersion led to formation of networks between nano ZnO and polymer chains. Occurrence of dielectric interfacial relaxations reduced upon control of dispersion. Nonlinear electrical behavior and thermal behavior enhanced by networks formation. Excellent resistance to surface erosion of nanocomposites, improved up to 10 times. Abstract: Thermoplastic elastomer nanocomposites based on respectively polystyrene- b -poly(ethylene- co -butylene)- b -polystyrene (SEBS) and polystyrene- b -poly(ethylene- co -butylene)- b -polystyrene grafted maleic anhydride (SEBS-MA) block copolymers and containing functionalized zinc oxide (ZnO) nanoparticles have been investigated as candidate materials for high voltage (HV) insulation systems. The dispersion of the organically modified ZnO nanoparticles has been successfully tuned through the MA graft and the block copolymer nanostructure. In particular, nanocomposites with signs of rheological percolation, indicating the formation of a network between individually dispersed nanoparticles and polymer chains, have been obtained at ZnO content as low as 5 wt% (0.9 vol%). This behavior resulted in an enhancement of the thermal conductivity and better control of the electrical conductivity while maintaining breakdown strength and dielectric losses in the same range of the unfilled insulating matrices. Furthermore, the resistance to surface erosion by partial discharges was significantly improved: in the presence of 5 wt% of individually dispersed ZnO nanoparticles, the eroded volume was reduced 10 times.